Monitoring the KMT2A gene post‐chemotherapy independently predicts the relapse and survival risk after allogeneic haematopoietic stem cell transplantation - Liu, Jing; Zhao, Xiao‐Su; Chang, Ying‐Jun; Qin, Ya‐Zhen; Jiang, Qian; Jiang, Hao; Zhang, Xiao‐Hui; Xu, Lan‐Ping; Wang, Yu; Lv, Meng; Liu, Kai‐Yan; Huang, Xiao‐Jun; et al. (British journal of haematology, 2025)
Summary This study evaluated the kinetics of KMT2A‐r during chemotherapy and its impact on allogeneic haematopoietic stem cell transplantation (allo‐HSCT) outcomes. KMT2A‐r was assessed post‐induction (MRD1), after the first (MRD2) and second (MRD3) consolidations and pre‐transplant (MRD4) in 52 patients with acute myeloid leukaemia (AML). KMT2A‐r significantly decreased from diagnosis to MRD2 (p < 0.001 for diagnosis vs. MRD1; p = 0.019 for MRD1 vs. MRD2). The incidence of KMT2A‐r negativity (57.5%) peaked at MRD2. KMT2A‐r status at each time point significantly affected post‐transplant outcomes. Cluster analysis identified four KMT2A‐r kinetic profiles: persistently negative (−/−), turned negative at transplant (+/−), turned positive at transplant (−/+) and persistently positive (+/+). The (−/−) group had the best outcomes, with a cumulative incidence of relapse (CIR) of 13.0%, overall survival (OS) of 82.0% and leukaemia‐free survival (LFS) of 81.7%. The (+/+) group had the worst prognosis, with a CIR of 58.8%, OS of 29.4% and LFS of 23.5%. KMT2A dynamics were an independent risk factor for CIR (Hazard ratio [HR] = 11.070, 95%CI 2.395–51.165, p = 0.002), LFS (HR = 9.316, 95%CI 2.656–32.668, p < 0.001) and OS (HR = 7.172, 95%CI 1.999–25.730, p = 0.003). In conclusion, KMT2A‐r status after chemotherapy and its kinetics are significant HSCT prognostic indicators. KMT2A‐r kinetics during chemotherapy and its impact on allogeneic haematopoietic stem cell transplantation (allo‐HSCT) were unclear. KMT2A‐r levels were assessed in 52 acute myeloid leukaemia patients at four time points: post‐induction (MRD1), after first (MRD2) and second (MRD3) consolidations and pretransplant (MRD4). KMT2A‐r significantly decreased from diagnosis to MRD2 (p < 0.001 for diagnosis vs. MRD1; p = 0.019 for MRD1 vs. MRD2), with the highest incidence of negativity (57.5%) observed at MRD2. Cluster analysis identified four kinetic profiles: persistently negative (−/−), turned negative at transplant (+/−), turned positive at transplant (−/+) and persistently positive (+/+). The (−/−) group had the best outcomes (cumulative incidence of relapse (CIR): 13.0%, overall survival (OS): 82.0%, leukaemia‐free survival (LFS): 81.7%), while the (+/+) group had the worst prognosis (CIR: 58.8%, OS: 29.4%, LFS: 23.5%). KMT2A‐r dynamics were an independent risk factor for CIR (HR = 11.070, 95%CI 2.395–51.165, p = 0.002), LFS (HR = 9.316, 95%CI 2.656–32.668, p < 0.001) and OS (HR = 7.172, 95%CI 1.999–25.730, p = 0.003). In conclusion, KMT2A‐r status and kinetics are significant prognostic indicators for HSCT outcomes.